2011
DOI: 10.22342/jme.2.2.750.215-230
|View full text |Cite
|
Sign up to set email alerts
|

A Concrete Situation For Learning Decimals

Abstract: Learning about decimals is an important part in mathematics. However at the same time, decimals are known as the abstract numbers for students. Mostly in Indonesia, decimal is taught only as another notation for fractions or percentages. There are no meaningful references for them such as the use of concrete situations. This study aimed at investigating one situation that enables students to learn about decimals in a meaningful way, i.e. measurement activities. Design research was chosen to reach the research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 1 publication
0
8
0
2
Order By: Relevance
“…Furthermore, it is stated that in fact, the results of the tests showed that most students lacked comprehending of the basic skills that they should have studied in primary school and in daily life problems. The meaningful context can promote students' learning from informal level to preformal level consisting mathematical ideas (Pramudiani et al, 2011).…”
Section: State Of the Artmentioning
confidence: 99%
“…Furthermore, it is stated that in fact, the results of the tests showed that most students lacked comprehending of the basic skills that they should have studied in primary school and in daily life problems. The meaningful context can promote students' learning from informal level to preformal level consisting mathematical ideas (Pramudiani et al, 2011).…”
Section: State Of the Artmentioning
confidence: 99%
“…Kegiatan ini sejalan dengan pendapat Freudenthal bahwa pembelajaran matematika yang dipelajari karena matematika merupakan aktivitas manusia dan bukanlah suatu ilmu yang dipindah dari guru ke siswa. Hal ini sejalan dengan pendapat Caruth (2019) bahwa proses aktif yang memungkinkan siswa dalam memahami pembelajaran sesuai pengetahuan yang dimiliki sehingga pembelajaran menjadi bermakna bagi siswa (Pramudiani, 2011) dapat memengaruhi kemandirian belajar siswa.…”
Section: Menyelesaikan Permasalahanunclassified
“…Proses aktif akan memungkinkan siswa dalam melaksanakan pembelajaran disesuaikan dengan pengetahuan yang dimilikinya sehingga siswa dapat mandiri dalam belajarnya (Caruth, 2019). Kontekstual yang dimaksud yaitu dengan menghubungkan permasalahan di kehidupan sehari-hari siswa dengan materi yang akan dipelajari sehingga pembelajaran menjadi suatu pembelajaran yang bermakna bagi siswa (Pramudiani et al, 2011). Selain itu, kemandirian dapat didefinisikan sebagai suatu tindakan yang tidak bergantung dengan orang lain dalam menyelesaikan permasalahan terkait tugas belajarnya (Kemendiknas, 2010).…”
unclassified
“…Indonesian textbooks commonly consist of the tasks full of mathematics role and algorithms (Zulkardi, 2002;Pramudiani, Zulkardi, Hartono, van Amerom, 2011). In solving the beads problem, the pupils try to find the best strategy to find the amount.…”
Section: Intertwinement;mentioning
confidence: 99%